Vaping in adolescents: epidemiology and respiratory harm - Hamberger, Eric Stephen (Curr Opin Pediatr, 2020)
PURPOSE OF REVIEW: This review highlights epidemiologic changes in e-cigarette use in adolescents, discusses recent advances in aerosolized nicotine delivery, and provides and updated profile of research related to the lung-specific harm of e-cigarettes. RECENT FINDINGS: In the past decade, nicotine-containing e-cigarettes have emerged as the most popular tobacco and nicotine delivery modality among adolescents in the United States.(1) The surge in popularity of these devices has coincided with an outbreak of vaping-related lung injury, bringing e-cigarette use to national attention, and creating a great deal of confusion regarding their potential for respiratory harm. Newer pod-based devices and formulations of e-liquids have resulted in products appeal to youth and deliver nicotine with increasing efficiency. E-liquid aerosols are associated with direct harm to respiratory epithelium and have been shown to alter pulmonary function, inflammation, mucociliary clearance, and lung histology. SUMMARY: Although the long-term harms of regular e-cigarette use are unknown, numerous studies including early longitudinal data suggest e-cigarette use is associated with incidence of respiratory disease, independent of concurrent traditional cigarette use. Improved understanding and recognition of harm will contribute to the basis of further studies examining the role of e-cigarettes on chronic respiratory disease and will inform future prevention education.